2021
DOI: 10.1080/14756366.2021.1955873
|View full text |Cite
|
Sign up to set email alerts
|

The role of mTOR in age-related diseases

Abstract: The ageing population is becoming a significant socio-economic issue. To address the expanding health gap, it is important to deepen our understanding of the mechanisms underlying ageing in various organisms at the single-cell level. The discovery of the antifungal, immunosuppressive, and anticancer drug rapamycin, which possesses the ability to extend the lifespan of several species, has prompted extensive research in the areas of cell metabolic regulation, development, and senescence. At the centre of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 245 publications
2
26
0
Order By: Relevance
“…Stresses linked to hallmarks of aging (see mTORC1 and Age-Related Stressors ) impinge on mTORC1 activity and SG formation (see SGs and mTORC1 Signaling ). Conversely, enhanced mTORC1 signaling ( Papadopoli et al, 2019 ) and SG formation ( Cao et al, 2020 ) have been linked to age-related processes, and MTOR and SG levels often correlate with the severity of age-related diseases ( Papadopoli et al, 2019 ; Liu and Sabatini, 2020 ; Chrienova et al, 2021 ). However, the crosstalk between mTORC1 and SG formation in the context of aging progression is poorly explored.…”
Section: Discussionmentioning
confidence: 99%
“…Stresses linked to hallmarks of aging (see mTORC1 and Age-Related Stressors ) impinge on mTORC1 activity and SG formation (see SGs and mTORC1 Signaling ). Conversely, enhanced mTORC1 signaling ( Papadopoli et al, 2019 ) and SG formation ( Cao et al, 2020 ) have been linked to age-related processes, and MTOR and SG levels often correlate with the severity of age-related diseases ( Papadopoli et al, 2019 ; Liu and Sabatini, 2020 ; Chrienova et al, 2021 ). However, the crosstalk between mTORC1 and SG formation in the context of aging progression is poorly explored.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mTORC1 activity has long been known to increase both health‐ and lifespan and to slow biological ageing [ 96 ]. Experiments from the 1930s showed that rats exposed to calorie restriction lived for longer compared with rats that consumed an ad libitum diet [ 97 ].…”
Section: Living Longer and Healthier Through Inhibition Of Mtorc1mentioning
confidence: 99%
“…Previously, we demonstrated that SV40 polyoma virus T antigen might disrupt metabolism involving carbohydrates, amino acids, and nucleotides in the spontaneous lens tumor of transgenic mice ( 33 ) in line with the present findings. The two targets of mTOR (p70S6 kinase and 4EP1/2) modulate ribosome biogenesis and the metabolism of glucose and lipids ( 34 ). In this study, low expression of mTOR and its phosphorylated form in T-expressing spontaneous liver and pancreatic tumors might account for the dysfunctional effects of T antigen on biosynthesis, which was seen in our investigation.…”
Section: Discussionmentioning
confidence: 99%